Effect of temperature on simultaneous separation and extraction of hemicellulose using p-toluenesulfonic acid treatment at atmospheric pressure. (March 2022) - Feng, Chengqi; Zhu, Jiatian; Hou, Yajun; Qin, Chengrong; Chen, Wangqian; Nong, Yuhao; Liao, Zhangpeng; Liang, Chen; Bian, Huiyang; Yao, Shuangquan
Graphical abstract: Highlights: Bagasse hemicellulose was extracted efficiently by p -toluenesulfonic acid treatment. The separation yield of hemicellulose was 73.23%. The extraction yield of hemicellulose was 36.02%. The purity of extraction hemicellulose was 95.60%. Abstract: Hemicelluloses were effectively separated using p -toluenesulfonic acid ( p -TsOH) treatment at high temperature. High temperature and pressure promoted hydrolysis of hemicellulose, which limited its value upon recovery. In this study, bagasse hemicellulose was separated and extracted by p -TsOH treatment at atmospheric pressure. The effects of temperature, p -TsOH concentration, and time on hemicellulose separation and extraction were investigated. The optimal conditions were 80 °C, 3.0% p -TsOH, and 120 min. The separation and extraction yield of hemicellulose was 73.23% and 36.02%, respectively. Extraction hemicellulose with 95.60% purity was obtained. In addition, the dissolution mechanism of hemicellulose was analyzed. Degradation of β-glycosidic bonds was inhibited. Benzyl ether bond between carbohydrates and lignin was selectively cleaved. The skeleton structure of xylan in hemicellulose was protected while the functional groups of branch chain were severely damaged. It provides a valuable theoretical basis for the efficient separation and extraction of hemicellulose.